DESCRIPTIVE STUDY ON TEACHING READING TO THE EIGHTH GRADE STUDENTS OF SMP MUHAMMADIYAH 4 SURAKARTA IN 2015/2016 ACADEMIC YEAR - Munika, Oktavia Dwi (JoLLIET, 2016)
This research paper is intended to describe the teaching reading to the eighthgrade students of SMP Muhammadiyah 4 Surakarta in 2015/2016 AcademicYear. The writer focuses on teaching reading at the first semester conductedby the teacher. The purpose of this research is to know the methods forteaching reading used by the teacher and to know the problems faced by theteacher in teaching reading at the eighth grade of SMP Muhammadiyah 4Surakarta in 2015/2016 Academic Year. The data are taken from allelements of teaching reading conducted by the teacher and the students and other sources such as field note, syllabus, textbook, and lesson plan. Themethods of collecting data are observation, interview, and documentation.The result of the research shows that the methods of teaching reading usedby the teacher at the eighth grade of SMP Muhammadiyah 4 Surakarta in2015/2016 academic year are Grammar Translation Method, Direct Method,and Cognitive Code Language. The problems of teaching reading are limitedstudentsâ vocabulary, uncontrolled class situation, and limited media used. Key words: descriptive study, teaching reading